A potent transrepression domain in the retinoblastoma protein induces a cell cycle arrest when bound to E2F sites. - William R. Sellers; J W Rodgers; William G. Kaelin (1995)
An intact T/E1A-binding domain (the pocket) is necessary, but not sufficient, for the retinoblastoma protein (RB) to bind to DNA-protein complexes containing E2F and for RB to induce a G1/S block. Indirect evidence suggests that the binding of RB to E2F may, in addition to inhibiting E2F transactivation function, generate a complex capable of functioning as a transrepressor. Here we show that a chimera in which the E2F1 transactivation domain was replaced with the RB pocket could, in a DNA-binding and pocket-dependent manner, mimic the ability of RB to repress transcription and induce a cell cycle arrest. In contrast, a transdominant negative E2F1 mutant that is capable of blocking E2F-dependent transactivation did not. Fusion of the RB pocket to a heterologous DNA-binding domain unrelated to E2F likewise generated a transrepressor protein when scored against a suitable reporter. These results suggest that growth suppression by RB is due, at least in part, to transrepression mediated by the pocket domain bound to certain promoters via E2F.